The Tettigoniidae (Orthoptera) described by Salvador de Toledo Piza Jr. and deposited in the collection of the University of São Paulo, Escola Superior de Agricultura "Luiz de Queiroz", Brazil - Chamorro-Rengifo, Juliana; Braun, Holger (Zootaxa, 2010)
The type specimens of Tettigoniidae described by S. de Toledo Piza were photographed for Orthoptera Species File Online and examined. As a result of this revision several species are moved to different genera and two species to different subfamilies, 20 genera and 10 species are synonymized, one species is resurrected from synonymy, and two new genera are created, each accommodating a unique species described by Piza: Toledopizia gen. nov. (Conocephalinae: Copiphorini) and Pizatettix gen. nov. (Pseudophyllinae: Platyphyllini). In total there are 32 new combinations of species names. The paper includes a checklist and explanations for all nomenclatural changes.